IDENTIFICATION OF STUDENT ERRORS IN SOLVING THE PROBLEM ON THE MATERIAL OF COMPOSING AN EQUIVALENT Force IN THE TENTH GRADE OF CONSTRUCTION AND PROPERTY BUSINESS SMK NEGERI 1 PALANGKA RAYA - Hari Fansyah; Pantur Pandiangan; Samuel Layang (PARENTAS: Jurnal Mahasiswa Pendidikan Teknologi dan Kejuruan, 2021)
The material of composing an equivalent force became the focus of this study. Researcher want to see deeper and broader understanding of students related to this material. One teacher's information that most students make mistakes in solving the problem in the form of a description on the subject of engineering mechanics. The purpose of this study is to describe the mistakes made by students in completing the description of the material in composing an equivalent force in the thenth grade of Construction and Property SMK Negeri 1 Palangka Raya. This research uses descriptive method with qualitative approach. Population in this research is thenth grade of Business of Construction and Property of SMK Negeri 1 Palangka Raya is 23 people. Sampling by purposive sampling so chosen 4 subject of students with criterion of student can represent every aspect in making mistake that is mistake in comprehension problem, make mathematical model, calculation and draw conclusion, and able to communicate well. Data collection was done by test and interview method. From the research obtained the average result of the percentage of students who make mistakes in the aspects of understanding the problem of 5.44%, the error occurs because students do not write a complete what is known and asked in the matter. For the aspect of making a mathematical model of 21.74%, though students can write what is known and asked from the test questions but students are not able to change what is known into the mathematical model. For the calculation aspect of 35.87%, the error occurs due to wrong students in addition and calculation in the form of the root so that the results obtained are not appropriate. Students do not include a unit symbol into the calculation process. For Aspects to draw conclusions of 90.2%, errors occur because students do not write conclusions and students do not return answers into context questions, this can be seen from the answers of students who are less precise.